A literature review: physicaltherapy of the hip after septic arthritis - Andrei Maxim (Balneo Research Journal, 2018)
Introduction. Septic arthritis is one of the most common osteo-articular infections encountered in pediatric orthopedic pathology. Due to the difficult diagnosis and secondary complications of late diagnosis and a late-established treatment, recovery of these patients is very difficult, and long-term outcomes are not always the best. Materials and methods. We used the electronic databases and selected articles that had as main topic recovery and rehabilitation after septic hip arthritis and evaluation methods of treatment. Results. The start of physiotherapy and recovery and rehabilitation treatment after medical or surgical treatment has not yet been accurately established. Various manual handling techniques, muscle stretching exercises, and articular mobility enhancement exercises aim to improve the quality of life of patients with septic osteoarthritis. Conclusion. A good collaboration between the orthopedic surgeon and the physiotherapist will lead to a good functional result and the ultimate goal of this collaboration is a life as close to normal as possible for the patient.